27 ASSOCIATIONS BETWEEN ORTHOSTATIC BLOOD PRESSURE BEHAVIOUR AND PROGRESSION OF AGE-RELATED MACULAR DEGENERATION IN THE IRISH LONGITUDINAL STUDY ON AGEING (TILDA). (25th October 2022) - Connolly, E; Doyle, SL; Kenny, RA; Romero-Ortuno, R
Abstract: Background: Age-Related Macular Degeneration (AMD) is a progressive disease and the leading cause of vision loss in over 50's in developed countries. Age-related changes in the neuro-cardiovascular system, at times manifesting as exaggerated blood pressure drops on standing (orthostatic hypotension) may be associated with end-organ damage. The aim of this study was to examine if the pattern of recovery of blood pressure upon standing from a supine position (orthostatic blood pressure behaviour), was associated with progression of AMD. Methods: We utilised data from TILDA participants who had AMD at the wave 1 health assessment and returned for retinal image grading during the wave 3 health assessment, four years later. Beat-to-beat BP data was measured non-invasively by digital photoplethysmography (Finometer® MIDI) during the wave 1 Active Stand (AS) test. Measures recorded during AS included Systolic (SBP) and Diastolic (DBP) blood pressure. Associations between systolic and diastolic orthostatic BP behaviour and AMD progression were examined using generalised linear models (GLM). Baseline characteristics were compared between progression groups with the 2-samples Mann-Whitney U test and the Chi-squared test. Results: Of the 191 included participants, 46 (24%) were found to have progression of AMD, while 145 (76%) had no change or regression of the disease. GLMs revealed no significant differences in SBP orthostatic behaviour across groups. However, those with AMD progression had lower orthostatic DBP values (tests of between-subjects effects p=0.005), particularly between 30-60 seconds post-stand (AMD progression: 72±10mmHg vs. No AMD progression: 79±12mmHg; p<0.001). Of the baseline participant characteristics considered, only age was associated with AMD progression (AMD progression: 66±8yrs vs. No AMD progression: 62±9yrs; p=0.005). Conclusion: In this sample of TILDA participants with AMD, lower orthostatic DBP values were associated with AMD progression over four years. Reduced orthostatic diastolic perfusion may be a novel modifiable risk factor for AMD progression.